1
$\begingroup$

Tangents are drawn to the circle $x^2+y^2=a^2$ from a point which always lies on the line $lx+my=1$. Prove that the locus of the mid point of chords of contact is $x^2 + y^2 -a^2(lx+my)=0$

My Attempt::

let mid point of chord of contact be $(h, k)$ & point $(x1, y1)$ be always lying on line: $lx+my=1$ then we have $lx_1+my_1=1$ ...(1) Now equation of chord of contact to circle: $x^2+y^2=a^2$ is $xx_1+yy_1=a^2$ but $(h, k)$ lies on chord of contact hence satisfying equation of chord gives us $hx1+ky1=a^2$ .......(2)

Please help me to complete this proof .

$\endgroup$
2
  • $\begingroup$ @@@Kanwaljit Singh, Could you please help me with this problem? $\endgroup$
    – pi-π
    Feb 1 '17 at 0:19
  • $\begingroup$ Observe that this midpoint is the circular inverse of the point on the line, so the resulting curve is the circular inversion of $lx+my=1$. $\endgroup$
    – amd
    Dec 16 '17 at 8:39
3
$\begingroup$

enter image description here

You can write the equation of the polar line (green line in the figure):

$$x_1x+y_1y=a^2$$

where $(x_1,y_1)$ is a point of the line $lx+my=1$ (red line).

The equation of the normal (blue line) to the polar line, passing through $(x_1,y_1)$ is:

$$y={y_1\over x_1}x$$

so we can find the middle point $M$ of the chord:

\begin{cases}x_1x+y_1y=a^2\\y={y_1\over x_1}x\end{cases}

Solving this system, we get:

$$M\left(x_M={a^2x_1\over x_1^2+y_1^2},y_M={a^2y_1\over x_1^2+y_1^2}\right)$$

Now we must eliminate $x_1$ and $y_1$, thus:

\begin{cases}x_M={a^2x_1\over x_1^2+y_1^2}\\y_M={a^2y_1\over x_1^2+y_1^2}\\lx_1+my_1=1\end{cases}

Squaring and adding the first and the second equation:

\begin{cases}x_M^2+y_M^2=a^4{x_1^2+y_1^2\over (x_1^2+y_1^2)^2}={a^4\over x_1^2+y_1^2}\\x_M={a^2x_1\over x_1^2+y_1^2}\\y_M={a^2y_1\over x_1^2+y_1^2}\\lx_1+my_1=1\end{cases}

\begin{cases}{x_M^2+y_M^2\over a^2}={a^2\over x_1^2+y_1^2}\\x_M={x_M^2+y_M^2\over a^2}x_1\longrightarrow a^2x_M=(x_M^2+y_M^2)x_1\\y_M={x_M^2+y_M^2\over a^2}y_1\longrightarrow y_M={x_M^2+y_M^2\over a^2}{(1-lx_1)\over m}\longrightarrow a^2my_M-(x_M^2+y_M^2)=-(x_M^2+y_M^2)lx_1\\y_1={1-lx_1\over m}\end{cases}

so $a^2my_M-(x_M^2+y_M^2)=-a^2lx_M\longrightarrow x_M^2+y_M^2-a^2(lx_M+my_M)=0$.

$\endgroup$
5
  • $\begingroup$ @@MattG88, Is this the continuation of my process? $\endgroup$
    – pi-π
    Feb 1 '17 at 0:41
  • $\begingroup$ Yes it could be;-) $\endgroup$
    – MattG88
    Feb 1 '17 at 0:42
  • $\begingroup$ @@MattG88, I could not understand clearly. Could you please say me what background knowledge is needed to tackle it? $\endgroup$
    – pi-π
    Feb 1 '17 at 0:46
  • $\begingroup$ I suppose that you need to know the equation of a line through a point, the equation of a polar line, the relation between the angular coefficients of two normal lines...I think it is enough;-) $\endgroup$
    – MattG88
    Feb 1 '17 at 1:01
  • $\begingroup$ However it also depends by the approach you want to use, it is possible to solve this problem applying the Euclid's theorem... $\endgroup$
    – MattG88
    Feb 1 '17 at 1:07

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.